Examining the linkages between employee brand love, affective commitment, positive word-of-mouth, and turnover intentions: A social identity theory perspective. Issue 1 (March 2022) - Mittal, Shweta; Gupta, Vishal; Motiani, Manoj
Abstract: Brand love has largely been examined from a customer perspective and seldom from an employee perspective. Drawing on the social identity theory, this study attempts to examine employee brand love and its relationship with affective commitment, positive word-of-mouth (PWOM) behaviour, and turnover intention. Using a sample of 289 professionals from public and private sector insurance companies in India, we find that employee brand love has a significant positive effect on affective commitment and PWOM, as well as a significant negative effect on turnover intention. Furthermore, affective commitment mediates the relationship of employee brand love with PWOM and turnover intention. Implications for theory and practice are discussed.